Learning Outcomes of Information Technology Competency Promoting Activities (SSPC) on Principles of Software Development Subject of Computer Program Kalasin University - Sinlapaninman, Unyaparn (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2020)
The objectives of the research article were 1) to study the effectiveness index of the information technology competency promotion activities (SSPC), and 2) to study their satisfaction with their learning from the information technology competency promotion activities (SSPC). The purposive sample consisted of 20 second year Computer major students Faculty of Education and Educational Innovations at Kalasin University, selected by Purposive Sampling. The research instruments were: 1) an achievement test, 2) a satisfaction questionnaire. Statistics in analyzing the data were percent, arithmetic mean, standard deviation, and effectiveness Index. The results of research were found that: 1) The efficiency of the information technology competency promotion activities (SSPC) was higher, 2) the effectiveness index of the information technology competency promotion activities (SSPC) was high and 3) Regarding satisfaction, the study revealed that their average satisfaction with their satisfaction with their learning from the information technology competency promotion activities (SSPC) in the overall was high level.